SOCIAL MECHANISMS OF EMPLOYMENT PROVISION - Абдувохидов Аббос Бекзодович, Bakirova Nargiza Batriraliyevna (Bright Mind Publishing, 2025)
This article analyzes the social mechanisms of the employment process. The role of employment policy, labor market institutions, and the social protection system is considered. It also highlights methods of employment promotion, public-private partnership, and the importance of the education and training system. The article also studies international experience in increasing employment and provides recommendations using the example of Uzbekistan.
Keywords: Employment, labor market, social mechanisms, employment, labor migration, social protection, state policy.